Tipologi Kepemimpinan Kepala Sekolah dalam Mewujudkan Sekolah Ramah Anak - Arkam, Rohmad; Sulistyorini (Institut Agama Islam Negeri Madura, 2024)
This research aims to identify the typology of leadership possessed by school principals in creating a child-friendly school, TK Muslimat NU 089 Kepatihan Ponorogo. The method used in this research is descriptive qualitative type. Data collection using interview, observation and documentation techniques. The results of this research show that the leadership typology of the Muslimat NU 089 Kepatihan Ponorogo Kindergarten principal in creating a child-friendly school is in line with the transformative leadership typology. This can be proven from the results of interviews and observations at Muslimat NU 089 Kepatihan Kindergarten, Ponorogo Regency, building communication and collaboration with parents and the community. With good communication, school principals can strengthen school policies in creating child-friendly schools. Apart from that, parents and the community are also given the freedom to supervise all existing programs at school in accordance with the principles of child-friendly schools. Abstrak